2019
DOI: 10.14434/ijdl.v11i1.24264
|View full text |Cite
|
Sign up to set email alerts
|

Design Challenges for Science Games:

Abstract: The abstract nature of quantum mechanics makes it difficult to visualize. This is one of the reasons it is taught in the language of mathematics. Without an opportunity to directly observe or interact with quantum phenomena, students struggle to develop conceptual understandings of its theories and formulas. In this paper we present the process of designing a digital game that supplements introductory quantum mechanics curricula. We present our design process anchored on three key challenges: 1) drawing upon s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Games in particular show promise in introducing new concepts and teaching some basics on quantum mechanics, which has inspired the development of educational games and learning platforms integrating games with learning material [78,79,80]. These simulation tools have been proven efficient for educational purposes [68,69,81,82,83,84,85] as well as for research settings as shown by the Science at Home team with their 2021 study on using the visualisation and simulation tool Quantum Composer [86].…”
Section: History Of Quantum Gamesmentioning
confidence: 99%
“…Games in particular show promise in introducing new concepts and teaching some basics on quantum mechanics, which has inspired the development of educational games and learning platforms integrating games with learning material [78,79,80]. These simulation tools have been proven efficient for educational purposes [68,69,81,82,83,84,85] as well as for research settings as shown by the Science at Home team with their 2021 study on using the visualisation and simulation tool Quantum Composer [86].…”
Section: History Of Quantum Gamesmentioning
confidence: 99%
“…It has been noted that allowing scientific experimentation is an important part of fostering scientific inquiry [33], and in the quantum realm, such experimentations are not readily available for the majority of the population. Hence, properly designed games [34] can be used to close this gap to some extent. We believe that it is timely to dig into this topic in systematic, critical, and rigorous manner to unveil opportunities and criticalities, and elaborate through a theoretical and practical perspective various physics education research tools.…”
Section: Introductionmentioning
confidence: 99%